Development and Validation of the RP-HPLC Method for Dexamethasone Sodium Phosphate Determination in Nasal Chitosan Microsphere Preparations - Desnita, Rise; Noviana, Eka; Zai, Khadijah; Sulaiman, Teuku Nanda Saifullah (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The purpose of this work was to provide a robust, sensitive, accurate, and straightforward analytical method for measuring dexamethasone sodium phosphate (DSP) in chitosan microspheres preparedn using the spray drying method. DSP was quantitatively analyzed using RP-HPLC with an ultraviolet detector at 254 nm, a mobile phase that contained a mixture of acetonitrile and 0.1% sodium dihydrogen phosphate monohydrate (50:50) operating isocratically at a flow rate of 1.0 mL/min, and a stationary phase that was a C18 PrincetonSPHER-100 C18-QB 100A HPLC Column (250 × 4.6 mm, 5 um). The ICH recommendations were followed in the validation of the analytical method. DSP had a retention duration of 2.899 minutes and a tailing factor of 0.827. The RP-HPLC method was linear (R = 0.9992) in the 15-60 ug/mL concentration range. The limits of quantitation (LOQ) and detection (LOD) were 4.425 ug/mL and 1.327 ug/mL, respectively. The relative standard deviations for the intra-day and inter-day precisions were 0.057-0.876% and 0.780-0.949%, respectively. The recovery percentages at 50, 100, and 200% concentration levels were within the 99.269-100.980% range. The validated method has been successfully applied to determine DSP entrapment efficiency in chitosan microspheres. A linear, sensitive, accurate, precise, and robust technique of determining DSP in chitosan microsphere preparations is offered by the established RP-HPLC method.